(untitled) (Research, Society and Development, 2022)
Effluents from conventional intensive aquaculture, based on high water exchange, may strongly contribute to the acceleration of eutrophication processes, due to the significant nutrient load present in unconsumed foods and excreted waste. On the other hand, there are intensive and super-intensive systems for the cultivation of aquatic organisms that use water exchange associated with strong aeration and biological transformation of macronutrients. Such sustainable systems use the bio-addition of friendly microorganisms to increase the rate of degradation of macronutrients and maintain water quality. A mathematical adjustment was used in this study to verify the dynamics of organic matter, nitrogen and phosphate during the experiment period. A pulse dynamic at regular times occurred indistinctly for all indicators evaluated in this study, although the intensity of the pulses showed particularities among the different indicators of water quality. Although the behavior of regular pulses of the indicators occurred, this condition did not affect the growth of fish subjected to a simulated system of intensive production associated with the bio-addition of friendly microorganisms.